2015
DOI: 10.1002/jcc.24242
|View full text |Cite
|
Sign up to set email alerts
|

Buckybowls as adsorbents forCO2, CH4, and C2H2: Binding and structural insights from computational study

Abstract: Noncovalent functionalization of buckybowls sumanene (S), corannulene (R), and coronene (C) with greenhouse gases (GGs) such as CO2 , CH4 (M), and C2 H2 (A) has been studied using hybrid density functional theory. The propensity and preferences of these small molecules to interact with the concave and convex surfaces of the buckybowls has been quantitatively estimated. The results indicate that curvature plays a significant role in the adsorption of these small molecules on the π surface and it is observed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 73 publications
(116 reference statements)
2
28
0
Order By: Relevance
“…In piperine@CB[7] there was 27 number of BCP's which can be classified into interactions such as,13 C=O⋅⋅⋅H and 13 N⋅⋅⋅H type, and one C⋅⋅⋅O=C type interaction. The heteroatom interactions in these systems were in the range of 0.007 to 0.011 a.u, which are well within those observed for the weak non‐covalent interactions . The Laplacian of electron density ∇ 2 ρ, at all the BCPs are negative, indicating the presence of covalent interaction between the guest and host molecule.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In piperine@CB[7] there was 27 number of BCP's which can be classified into interactions such as,13 C=O⋅⋅⋅H and 13 N⋅⋅⋅H type, and one C⋅⋅⋅O=C type interaction. The heteroatom interactions in these systems were in the range of 0.007 to 0.011 a.u, which are well within those observed for the weak non‐covalent interactions . The Laplacian of electron density ∇ 2 ρ, at all the BCPs are negative, indicating the presence of covalent interaction between the guest and host molecule.…”
Section: Resultssupporting
confidence: 76%
“…The measure of electron density (ρ) at the BCP provides the information about the nature and strength of bonding between the molecules in an inclusion complex . The sign of the Laplacian is determined by the energy that dominates in the bonding zone.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional technologies (such as ammonia scrubbing, solvent absorption) to remove these gases have certain disadvantages such as, high energy cost, corrosion, solvent loss, degradation, and byproducts production . The development of new materials, ionic liquids, and modification of industrial processes are an ongoing effort by researchers to efficiently capture these gases . Our ability to model these sorption processes using a first principles approach can have significant impact in speeding up the discovery process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be suggested that the Au-Pillarplex have more π bond character towards the guest molecules [40]. EDA analysis provides quantitate measurement, which would be useful to understand the nature of interaction in these complexes [41]. The total binding energies are decomposed into ΔE disp , ΔE Pauli , ΔE elstat , and ΔE orb terms.…”
Section: Electron Density and Energy Decomposition Analysismentioning
confidence: 99%